2014
DOI: 10.1007/jhep08(2014)044
|View full text |Cite
|
Sign up to set email alerts
|

The gravity dual of supersymmetric gauge theories on a squashed S 1 × S 3

Abstract: We present a new one-parameter family of supersymmetric solutions deforming AdS 5 . This is constructed as an asymptotically locally anti de Sitter (AlAdS) solution of five-dimensional minimal gauged supergravity, with topology R × R 4 and a non-trivial graviphoton field, and can be uplifted to ten or eleven dimensional supergravities. An analytic continuation of this solution yields the gravity dual to a class of four-dimensional N = 1 supersymmetric gauge theories on a curved manifold with topology S 1 × S 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(138 citation statements)
references
References 69 publications
(237 reference statements)
6
132
0
Order By: Relevance
“…Since the supersymmetric Casimir energy has an N 2 (in 4d) or N 3 (in 6d) scaling with the rank of the gauge group it is natural to expect that it should be also accessible by a holographic calculation. This was already discussed to some extent in [2,8] in four dimensions, but the precise holographic interpretation is not yet clear and deserves further study. It is tantalizing to speculate that there might be a connection between the supersymmetric Casimir energy for N = 4 SYM computed in section 4 above and some physical quantity for the Gutowski-Reall black hole [78,79] and its generalizations [80,81].…”
Section: Jhep09(2015)142mentioning
confidence: 89%
See 2 more Smart Citations
“…Since the supersymmetric Casimir energy has an N 2 (in 4d) or N 3 (in 6d) scaling with the rank of the gauge group it is natural to expect that it should be also accessible by a holographic calculation. This was already discussed to some extent in [2,8] in four dimensions, but the precise holographic interpretation is not yet clear and deserves further study. It is tantalizing to speculate that there might be a connection between the supersymmetric Casimir energy for N = 4 SYM computed in section 4 above and some physical quantity for the Gutowski-Reall black hole [78,79] and its generalizations [80,81].…”
Section: Jhep09(2015)142mentioning
confidence: 89%
“…This result was further clarified in [2,7] where it was shown that there are no finite counterterms and E is scheme-independent. The relation (1.3) was further studied in [8] where the authors discussed a holographic interpretation of this result. 1 We refer to the quantity E and its cousins for SCFTs in other even dimensions as the supersymmetric Casimir energy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On general grounds, we expect that they differ by local counter-terms and by Casimir energy factors (Casimir energy factors are indeed present, see for example [39,40]). Both of these effects necessarily scale like O(β), therefore they are inconsequential as far as the singular terms in β go.…”
Section: Hopf Surfacesmentioning
confidence: 99%
“…The holographic energy-momentum tensor T ij and R-symmetry current j i may be computed with standard formulas (see e.g. [7]). The former is particularly unwieldy, but we have verified that these satisfy the expected Ward identities.…”
Section: Dual Supergravity Solutionsmentioning
confidence: 99%